Prevalence of female genital tract tuberculosis in suspected cases attending Gynecology OPD at tertiary centre by various diagnostic methods and comparative analysis - Sharma, Diksha; Depan, Anju; Yadav, Kanti; Narayan, Suchitra; Sharma, Anubhav (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The genital tract tuberculosis is one of the most common causes of tubal factor infertility. This study was conducted to compare the results of different diagnostic methods used in screening for female genital tuberculosis in suspected cases attending Gynecology OPD at RMC, Ajmer. Methods: This prospective study was conducted in department of obstetrics and gynecology, J. L. N. Medical College, Ajmer, Rajasthan, for studying incidence of genital tuberculosis by various diagnostic methods (viz. AFB smear examination, AFB Lowenstein Jensen culture method, TB-PCR and CBNAAT). Results: Prevalence of genital TB was 5.5% in study population of 200 selected women meting the inclusion criteria. 72% women were in between 20-30 years age group. Oligomenorrhoea (24%) was found to be significant symptom with P value of <0.05. TBPCR and CBNAAT were found to be statistically significant with P value of <0.001 for diagnosing FGTTB. Conclusions: We concluded that genital tuberculosis is paucibacillary disease, TBPCR and CBNAAT appears to be rapid and sensitive diagnostic modality.